The Effect Of Question Prompt Scaffolding-Based Student worksheet On Scientific Writing Skills Of Junior High School Students In Science Learning - Rusdianto; Supeno; Ulin Nuha; Rizka Elan Fadilah; Adi Irawan (Postgraduate, University of Mataram, 2024)
Science learning is closely linked to students' scientific writing skills. While science education imparts scientific concepts and theories, scientific writing enables students to structure and express their understanding of these concepts and theories. Despite this, scientific writing skills among junior high school students tend to be in the low category. This study aimed to investigate the impact of using student worksheets based on question prompt scaffolding on the scientific writing skills of junior high school students. The research employed a quasi-experimental design with a post-test only control group. Data were collected using tests, with essay tests assessing scientific writing skills across various indicators such as clarification, observation, measurement, claims, causation, argumentation, and generalization. The results from an independent sample t-test indicated a significance value of p Sig. (2-tailed) of 0.028, which is less than 0.05, suggesting a significant difference in the average scientific writing scores between the experimental and control groups. Thus, it can be concluded that student worksheets based on question prompt scaffolding significantly enhance the scientific writing skills of junior high school students in science learning.